Interests of Gen Zs in rural communities: insights to strengthen the delivery of the Philippine PATH-Fit program - L. Tagare, Jr., Ruben; B. Esto, Jomar; Ann C. Tenebroso, Desiree; E. Inabangan, Jeahr; R. Pregunta, William; P. Acera, Erika; Lincoln C. Rivas, Jan; P. Avila, Claribel; Floyd M. Boyles, Pink (Institute of Advanced Engineering and Science, 2025)
This study investigated the local interests of Generation Z (Gen Z) students in rural communities to strengthen the delivery of the Philippine physical activity towards health and fitness (PATH-Fit) program. Using a qualitative-ethnographic approach, insights were gathered from 20 carefully selected Gen Z students through open-ended questions validated by experts. The findings revealed seven key areas of interest: i) social media, videos, and the internet; ii) something profitable; iii) e-games; iv) sports and physical activities; v) going out and exploring; vi) church, reflection, and music; and vii) rest and sleep. This study concludes that the local interests of Gen Z students in rural communities paint a comprehensive picture of a generation adeptly balancing the digital and physical realms of their lives. From the appeal of social media, online ventures, and e-games to the grounding effects of sports, nature exploration, and spiritual practices, these students demonstrate a flexible approach to well-being and personal growth. Their focus on profitable online activities reflects a pragmatic response to economic challenges, while their commitment to physical activities and outdoor exploration underscores the importance of maintaining a healthy lifestyle. Their emphasis on church, reflection, music, rest, and sleep also highlights a holistic understanding of mental and emotional health. Together, these interests reveal a resourceful, adaptive generation that is deeply aware of the need for balance in an increasingly complex world.